Problematika Proses Pembelajaran Pendidikan Agama Islam Di Era New Normal Pandemi Covid-19 - Siti Muawanatul Hasanah; Irfan Musadat (Qolamuna : Jurnal Studi Islam, 2021)
Abstract Problematika learning and the efforts to solve those problems in the new normal era of the covid-19 pandemic in islamic religious subjects at SD Plus Qurrota A'yun Malang. The research method used is a qualitative research method with a case study approach while for data collection by means of observation, interviews and documentation. The efforts to solve learning problems in the new normal era of the covid-19 pandemic online are building cooperation between the teacher, students themselves, and the parents, contacting students via phone or video call to carry out the TPQ learning process, students can do schoolwork manually (do the exercise in their workbooks), do thetring on other family members or join wifi to neighbors to carry out online learning. Meanwhile, problem solving about the efforts during offline learning are teachers using the allocation of time maximalize so than, Teachers can review the material that has been shared during online learning and provide standardization of health protocols for school residents. Keywords: Learning Islamic, Religious Education, in the New Normal